Distribution model of Iron (Fe) on Fe/Graphene Nano Sheets - Siburian, Rikson; Goei, Ronn; Manurung, Hana; Aritonang, Sri Pratiwi; Simanjuntak, Crystina; Hutagalung, Fajar; Anshori, Isa; Alias, Yatimah; Paiman, Suriati; Affi, Jon; Tok, Alfred Iing Yoong (Elsevier, 2023)
In this paper, we report about the distribution model of Iron (Fe) atoms on Graphene Nano Sheets (GNS). The purpose of this research is to evaluate the performance of Fe/GNS in terms of the distribution of Fe atoms on the graphene surface. GNS and Fe/GNS were prepared with modified Hummer’s and impregnation methods, respectively. We found that the morphology of graphite is different compare to GNS where GNS has thin layers and no stacking sheets (Scanning Electron Microscope (SEM) data) and it contains majority Carbon (C) element (more than 90 wt%) (EDX data). The X-Ray Diffraction (XRD) data of GNS shows the appearance weak and broad peak on 2θ = 26.6o indicating GNS was formed, and the sharp peaks on 2θ = 43.84o prove that Fe atoms are well deposited on GNS (XRD data). Both SEM and XRD data prove GNS produced and Fe deposited on GNS. Further, we propose the distribution model of Fe atoms on GNS surfaces based on three steps. The first step is the Fe precursor react with GNS to produce Fe ions. The second step is Fe ions reduce while being deposited on GNS surfaces, generating Fe clusters. Finally, Fe clusters migrate on the surfaces of GNS to form Fe particles. The smallest Fe crystal size in Fe/GNS is at 3.81% Fe (1.5009 nm) and distributed into GNS. Based on those data, GNS was found to affect the properties of Fe metal.